Degradation and encryption for outsourced PNG images in cloud storage. (2016) - Wang, Ying; Du, Jiali; Cheng, Xiaochun; Liu, Zheli; Lin, Kai
In cloud storage environment, users frequently store images and retrieve them by personal device, including mobile phones. However, the content of outsourced images will be leaked to the cloud server, which is not trusted by users. To protect the privacy of sensitive images, this paper proposes format-compliant degradation and encryption method for Portable Network Graphics (PNG). More specifically, for PNG degradation, improved prefix method and noise generation methods are developed. Furthermore, for PNG encryption, a modified generalised-Feistel method is developed. Finally, our security analysis demonstrates that the proposed scheme is secure. Our experiment results also show that the scheme is efficient and practical.